Air cavity-based vibrational piezoelectric energy harvesters - A. A. Mohamad Yusoff (National Technical University "Kharkiv Polytechnic Institute", 2021)
Introduction. Known vibrational energy harvesting methods use a source of vibration to harvest electric energy. Piezoelectric material works as a sensing element converted mechanical energy (vibration) to electrical energy (electric field). The existing piezoelectric energy harvesting (PEHs) devices have low sensitivity, low energy conversion, and low bandwidth. The novelty of the proposed work consists of the design of PEH’s structure. Air cavity was implemented in the design where it is located under the sensing membrane to improve sensitivity. Another novelty is also consisting in the design structure where the flexural membrane was located at the top of electrodes. The third novelty is a new design structure of printed circuit board (PCB). The purpose of improvised design is to increase the stress in between the edges of PEH and increase energy conversion. With the new structure of PCB, it will work as a substrate that absorbs surrounding vibration energy and transfers it to sensing element. Methods. Three techniques were successfully designed in PEH and fabricated namely PEH A, PEH B, and PEH C were characterized by two experiments: load and vibration. The load experiment measured load pressure towards the PEH, whereas the vibration experiment measured stress towards the PEH. Results. PEH C has the highest induced voltage for a weight of 5.2 kg at the frequency of 50 Hz and the highest stored voltage for a period of 4 min. The three techniques applied in PEHs were showed improvement in transducer sensitivity and energy conversion. Practical value. A piezoelectric acoustic generator was used in the experiment to compare the performance of the designed PEH with available piezoelectric transducers in the market. The new flexible membrane worked as a sensing element was worked as a cantilever beam. PVDF was used as a sensing element due to the flexibility of the polymer material, which is expected to improve sensitivity and operating bandwidth.